Effect of burnout among physicians on observed adverse patient outcomes: a literature review - Kashan Yasin Mangory; Lavin Yadgar Ali; Karin Isaksson Rø; Reidar Tyssen (BMC, 2021)
Abstract Background Physician burnout has potentially harmful effects for both physicians and their patients. Despite relationships between physician burnout and lowered patient satisfaction and clinician-rated adverse patient outcomes, there is scarce literature regarding effects on objective patient outcomes. This study aimed to examine the relationship between physician burnout and observed adverse patient outcomes via a review of the literature. Methods A search was performed on the MEDLINE, EMBASE and PsychINFO databases, using keywords and Medical Subject Headings. The identified studies were in English, published from 2007 to 2019, measured burnout among physicians using the Maslach Burnout Inventory (MBI), and included observed adverse patient outcomes. In total, 360 eligible articles were identified, and 11 were included in the final review. All included studies measured patient outcomes by observed clinical measures (e.g. quality of care and medical errors). Results Four studies found a clear significant relationship between physician burnout and observed adverse patient outcomes, while 6 did not. One study found a significant relationship with one of the MBI subscales. Burnout was, in contrast to depression, only partly associated with observed patient outcomes. Conclusions This review illustrates the need for a validation of physician burnout measured by MBI with respect to observed patient outcomes. Further studies are required to investigate the effects of physician burnout on observed quality of their patient care.